The impacts of soil enthalpy change on land–atmosphere interactions of permafrost on the Qinghai-Tibet Plateau - Ren Li; Shenning Wang; Junjie Ma; Wenhao Liu; Tonghua Wu; Changwei Xie; Xiaodong Wu; Yongjian Ding; Lin Zhao; Guojie Hu; Jimin Yao; Xiaofan Zhu; et al. (Geoderma)
The hydrothermal changes in the active layers of permafrost soils during freeze–thaw processes are crucial for understanding the interactions between the surface and the atmosphere. The soil enthalpy of the active layer in permafrost regions is a comprehensive parameter incorporating soil temperature and moisture, reflecting the energy state of the soil. Changes in soil enthalpy during freeze–thaw processes have important impacts on soil hydrothermal coupling processes and the land–atmosphere energy exchange. In this paper, using the measured hydrothermal data of the continuous permafrost region at Tanggula and the relict permafrost region at Mahanshan on the Qinghai-Tibetan Plateau, we analyzed the characteristics of soil enthalpy changes during freeze–thaw processes and discuss the hydrothermal coupling effects of soil enthalpy and land–atmosphere energy changes occurring during the processes and the lag relationship between soil enthalpy and precipitation. The soil enthalpy changes at the two sites were different, mainly due to their difference in water content. There is a near-linear relationship between soil enthalpy and unfrozen water content, with correlation coefficients greater than 0.9 at all depths, reflecting the phase change and migration of soil moisture. Soil enthalpy and net radiation at the surface displayed similar patterns, reflecting the balance of the surface energy budget. There was a 1–2 months lag relationship between the soil enthalpy of the whole active layer and precipitation, and this relationship varied with the season and the underlying surface.